FENOMENA KURS RUPIAH SEBELUM DAN SELAMA COVID-19 - Pebri Hastuti; La Ane; Melati Yahya (Fakultas Ekonomi Universitas Negeri Medan, 2020)
The COVID-19 pandemic was first announced by the government on March 2, 2020. COVID-19 has caused many impacts on various economic sectors in Indonesia. Not only in Indonesia but the impact of Covid-19 has disrupted world economic chains. In fact, it has the potential to cause an economic crisis in a number of countries if it is not dealt with quickly and appropriately. Especially in the exchange rate of the rupiah against the United States of America (US) which is increasingly weakening. This study aims to determine differences in the rupiah exchange rate before and during the co-19. The author uses library research instruments, documentation studies, internet browsing, where the data taken is secondary data from relevant agencies obtained from Bank Indonesia publications through Jakarta Interbank Spot Dollar Rate (Jisdor) data, data obtained from Jisdor is the rupiah exchange rate against the US dollar. This study uses quantitative methods with data analysis tools used are different test methods namely Wilcoxon Test with the help of the computer program SPSS Version 21. Where the data is taken from 7 November 2019 to 28 February 2020 before Covid-19 and during Covid-19 on March 2 until June 30, 2020. The method aims to find out significant differences between the rupiah exchange rates before and during the pandemic. The results of data processing showed that there were significant differences between the rupiah exchange rates before and during the pandemic. So it can be concluded that the spread of Covid-19 in the community will further weaken the exchange rate of the rupiah against the US Dollar.